Epigenomic landscape of melanoma progression to brain metastasis: unexplored therapeutic alternatives. (December 2015) - Marzese, Diego M; Witz, Isaac P; Kelly, Daniel F; Hoon, Dave SB
Melanoma brain metastasis is a complication with rising incidence. Despite the high rate of somatic mutations driving the initial stages of melanocyte transformation, the brain colonization requires a phenotypic reprogramming that is, in part, influenced by epigenomic modifications. This special report summarizes recent findings in the epigenomic landscape of melanoma progression to brain metastasis, with particular emphasis on the clinical utility of DNA methylation, chromatin modifications and ncRNA expression as theragnostic markers, as well as the significance of the metastatic microenvironment on melanoma brain metastasis epigenome.